APPLICATION OF TURBOCHARGER STAND CUTTING SYSTEMTOWARD IMPROVEMENT OF LEARNING ACHIEVEMENTSON MOTOR BENSIN - Prasetyo, Rachmat Adi; Mubarak, Ibnu; Noor, Ridwan Adam; Sriyono, S (Journal of Mechanical Engineering Education, 2020)
his study aims to determine the increase in learning achievement using a turbocharger system simulator on learning a turbocharger system. This research is motivated by the rapid development of technology in the turbocharger system, but the learning media in supporting the learning of the turbocharger system still has limitations. This media simulator is expected to improve the knowledge of the turbocharger system material, so that students' learning achievement can increase. This research is a research with pre-experimental design ¬ in the form of one-group pretest-posttest using a quantitative approach. The population in this study were 12 D-3 students in the automotive concentration class of 12 students. Sampling in this study is in accordance with the existing population, which is 12 people, with the term saturated sample because less than 100 people. The instrument used was a written test problem with 2 forms, namely pretest and posttest. The purpose of the test is to find out the increase in material insight into learning achievement before and after learning using the turbocharger system simulator media as treatment. The lowestpretest score obtained 25, while the highest score 27. Increased knowledge of the material on learning achievement increased after using the turbocharger system simulator media as treatment. The lowest posttest score obtained before the average score of the pretest obtained 26.08, after receiving treatment the average score got an increase from the posttest results obtained 76.25, with an N-gain score obtained 0.68 in the medium category.